Immune responses to viruses - Klenerman, Paul (Henry Stewart Talks, 2020)
The roles of adaptive immunity in responses to virus infection, Methods used to investigate role of T cells in immunity to infection in murine and human systems, LCMV as a model for antiviral responses and HCV parallels, Key mechanisms regulating CD8+ T cell responses in chronic infection, Induction of T cell responses as a possible vaccine strategy